Molar incisor hypomineralisation : new perceptions - Rios, Daniela; Santos-Pinto, Lourdes (Monographs in oral science / series editors M.A.R. Buzalaf, A. Lussi, 2024)
The book comprehensively discusses Molar Incisor Hypomineralisation (MIH), exploring whether it is a recent phenomenon or a newly recognized issue. It details developmental defects of enamel and the clinical characteristics of hypomineralised enamel. The book addresses the challenges of using scoring systems for MIH assessment and emphasizes the importance of comprehensive patient evaluation, including oral clinical records and behavior assessment. The impact of MIH on quality of life is discussed, alongside the post-eruptive breakdown of demarcated opacities. The prevalence and distribution of MIH and deciduous tooth hypomineralisation are covered, along with systemic and environmental risk factors and genetic theories. The book also addresses hypersensitivity and its management. It questions whether MIH is a risk factor for dental caries and if it is possible to remineralise hypomineralised enamel. The use of fissure sealants for managing hypersensitivity and post-eruptive breakdown in MIH-affected molars is discussed, along with adhesive challenges, esthetic restoration, and restorative possibilities for severely affected molars. Finally, the book highlights the rationale behind the extraction of hypomineralised first molars, the cost-effectiveness of MIH management, and the role of the internet in obtaining and sharing MIH-related information.